Strategi Pembelajaran Guru Pendidikan Agama Kristen dalam menghadapi Revolusi Industri 4.0 - Imayanti Nainggolan; Talizaro Tafonao; Agiana Her Visnhu Ditakristi; Yunardi Kristian Zega (MANTHANO: Jurnal Pendidikan Kristen, 2022)
Abstract: This article is a theoretical study of the learning strategies carried out by christian education teachers in the face of the industrial revolution 4.0. christian education teachers are part of educators who must play an active role in responding to the times. Therefore, teachers need to choose the right learning strategies for students in preparing cognitively, personally, and mentally. The learning strategies that can be carried out by Christian Education teachers in dealing with the industrial revolution 4.0 are such as strengthening character education, it is emphasized that christian education in schools not only requires students to understand and understand the Christian faith in terms of knowledge, but how students must experience spiritual and character transformation. Then the use of technology can make students think critically. Because it is able to solve problems that are happening and find sources of information from the internet. Furthermore, problembased learning can equip students to think critically to solve problems in everyday life. In addition, the use of e-learning media in learning has basic competencies that educators must have in implementing e-learning learning models. To achieve what the author's goal is, the author uses a qualitative method of library research, namely by collecting data and information related to the problem under study through journals, books, and several online media references that can be justified academically.Abstrak: Artikel ini adalah suatu kajian teoritis mengenai strategi pembelajaran yang dilakukan oleh guru PAK dalam menghadapi revolusi industri 4.0. Guru PAK merupakan bagian dari pendidik yang harus berperan aktif dalam meresponi perkembangan zaman. Oleh sebab itu, guru PAK perlu memilih strategi pembelajaran yang tepat bagi siswa dalam mempersiapkan kognitif, kepribadian, dan mental. Adapun strategi pembelajaran yang dapat dilakukan oleh guru PAK dalam mengahadapi revolusi industri 4.0 yaitu seperti penguatan pendidikan karakter kristen, hal ini ditekankan bahwa PAK di dalam sekolah tidak hanya menuntut siswa mengerti dan memahami iman Kristen dalam hal pengetahuan saja, akan tetapi bagaimana siswa harus mengalami transformasi spriritual dan karakter. Kemudian pemanfatan teknologi dapat membuat siswa berpikir kritis. Karena mampu memecahkan masalah yang sedang terjadi dan mencari sumber informasi dari internet. Selanjutnya pembelajaran Problem based learning dapat memperlengkapi siswa agar dapat berpikir kristis untuk menyelesaikan masalah dalam kehidupan sehari-hari. Selain itu penggunaan media e-learning dalam pembelajaran ada kompotensi dasar yang harus dimiliki pendidik dalam menyelenggarakan model pembelajaran e-learning. Untuk mencapai apa yang menjadi tujuan penulis ini, maka penulis menggunakan metode kualitatif kajian Pustaka, yaitu dengan menggumpulkan data-data informasi-informasi yang berhubungan dengan masalah yang diteliti melalui jurnal, buku, dan beberapa referensi media online yang dapat dipertanggung jawabkan secara akademik.